Association of preoperative cognitive frailty with postoperative complications in older patients under general anesthesia: a prospective cohort study - Jiamin Fang; Hao Liang; Muxin Chen; Yidi Zhao; Lin Wei (BMC Geriatrics)
Abstract Background Cognitive frailty (CF) is characterized by the coexistence of physical frailty and cognitive impairment, and it is associated with adverse health outcomes. Older adults are particularly vulnerable to CF due to factors such as age-related brain changes and the presence of comorbidities. Objective To investigate the effect of preoperative CF on postoperative complications in older patients. Methods This prospective cohort study was conducted among 253 patients aged 60–85 years, who underwent elective orthopedic and abdominal surgery (with a postoperative hospital stay of ≥ 3 days) at the Second Affiliated Hospital of Guangzhou University of Chinese Medicine from May 2023 to November 2023. CF was assessed using the Montreal Cognitive Assessment (MoCA) for the cognitive status and the Fried criteria for five frailty scales. Participants were split into four groups: Group A (neither frailty nor cognitive impairment), Group B (frailty without cognitive impairment), Group C (cognitive impairment without frailty), and Group D (cognitive frailty). The primary outcome was postoperative complications, while secondary outcomes included mobility disability, prolonged hospital stay (PLOS), re-operation and 90-day readmission. Results The median age (interquartile range) of participants was 69 (65–73) years, of which 40.3% were male. The prevalence of CF was 17.8%. The incidence of postoperative complications was 18.2% in Group A, 50.0% in Group B, 37.4% in Group C, and 75.6% in Group D. Multivariate analysis revealed that, compared to the control group (without cognitive impairment or frailty), patients with CF had a significantly higher risk of postoperative complications (OR, 12.86; 95%CI, 4.23–39.08). “Patients with frailty without cognitive impairment” had an increased risk (OR, 6.53; 95%CI, 2.04–20.9), while “those with cognitive impairment without frailty” also showed a higher risk (OR, 3.46; 95%CI, 1.57–7.64). Conclusions Cognitive frailty is significantly associated with an increased risk of postoperative adverse outcomes in older patients undergoing orthopedic and abdominal surgeries with general anesthesia. It indicates that clinicians should pay much attention to these older adults with CF.